Dielectric properties of lanthanum-doped CaCu3Ti4O12 synthesized by semi-wet route - Rai A.K.; Mandal K.D.; Kumar D.; Parkash O. (My University, 2025)
Effect of La3+ doping at Ca2+ site in CaCu3Ti4O12 has been examined. Compositions with x=0.10, 0.20 and 0.30 were synthesized in the system Ca(1-3x/2)LaxCu3Ti4O12 by semi-wet method. Powder X-ray diffraction confirmed the formation of monophasic compounds. The structure remains cubic similar to CaCu3Ti4O12. Lattice parameter increases slightly with increasing La3+ concentration. Microstructure has been studied using scanning electron microscopy (SEM). Average grain size is in the range 2-4 μm for various compositions. Energy-dispersive spectrometer (EDS) studies confirm the stoichiometry of the synthesized materials. Dielectric constant, dielectric loss and conductivity of the samples decrease with increasing lanthanum concentrations. © 2009 Elsevier Ltd. All rights reserved.